INSTRUCTIONS OF THE RASULULLAH ON FACTORS AFFECTING EDUCATION - Abdul Wahab Syakhrani; Salamah, Yuliana Erlin, Yunita (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Parents have a great influence in the education of their children. Children from birth have brought the perfect Islamic nature like a child born from its mother perfectly without the slightest flaw. The development of this Islamic nature depends on how the influence of education provided by parents, sometimes fosters, preserves and develops nature of Islam and sometimes turn it off and turn into a Jew, Christian or Magian. The obligation of parents is to educate children in accordance with the nature, they must not deviate and replace them with others.